STUDY OF BIO-MEDICAL WASTE GENERATION AND MANAGEMENT IN VARIOUS HOSPITALS IN DAVANGERE CITY OF KARNATAKA, INDIA - Thirumala, S. (Journal of Health and Allied Sciences NU, 2013)
This research article is to survey the practice of biomedical waste such as collection, storage, transportation and disposal along with the amount of generated biomedical waste in various hospitals in Davangere city, and create awareness among the staff and patient about biomedical wastes. The survey result on biomedical waste generation, disposal and methods adopted in various hospitals of Davangere city are discussed.
Keywords: Biomedical waste; Hospital waste; Davanagere city